Adventure to the planet Mars! - Marsh, Carole ([Peachtree City, Ga.] : Gallopade International/Carole Marsh Books, 2007)
Ms. Bogus travels with her class on a rocket field trip to Mars, where they learn about gravity and the landforms of the planet, but must be careful to dodge a few asteroids along the way.
"Includes five SAT words to know"--Cover.
4.8
3-6
Keywords: Rockets (Aeronautics) -- Juvenile fiction; School field trips -- Juvenile fiction; Rockets (Aeronautics) -- Fiction; School field trips -- Fiction; Rockets (Aeronautics) -- Fiction; Field trips -- Fiction; Mars (Planet) -- Juvenile fiction; Mars (Planet) -- Fiction; Mars (Planet) -- Fiction